"Pili torti et canaliculi" in a patient with X-linked ichthyosis, alopecia and teeth abnormalities. - Selvaag, E. (European Journal of Pediatric Dermatology, 2018)
We present a 15 year old boy with an X-linked ichthyosis, present since early cbildhood. In the last few months he has noticed hair loss. On investigation we found the typical findings of X-linked ichthyosis, with brownish-grey scaling on the trunk, extremities, neck and scalp. His hair felt stiff and dry, but was not more easily plucked than normal. The second premolars in the lower yaw (35 and 45) were missing, for which he during his adolescence received dental regulations. There were enamel defects on the left frontal tooth (31) in his lower yaw as well. The scanning electron microscopical investigation of his hairs showed twisting in combination with longitudinal grooves and ridges. The combination of these symptoms has not been described before.